The origins of the Michoacan civic pantheon, 1823-1834 (Tzintzun, Revista de Estudios Históricos, 2016)
Cultural history is one of the less frequented historiographical fields in the lines ofresearch that deal with Michoacan. This essay has the purpose of exploring some ofthe most representative aspects in this field in the entity, for the initial decades of theindependent period. From a generic approach on how the civic pantheon of moder-nity was set up, we also present the circumstances and historical conditions underwhich the first steps were taken in that regard. Largely the actions of this type in theentity, departed from the attention and imitation of the measures undertaken by thegeneral powers, to vindicate the main heroes of the war of independence. However,in the case of Michoacan proposals of heroization of figures such as Matamoros,Villalongin, Garcia Obeso and even Jose Maria Morelos, found strong resistancefrom members of the political class responsible to take decisions to institutionalizethem or not, therefore they had to deal with, in addition to the interference of theChurch, prejudices and resentments, explainable in good measured by the thenrecent performance in life of these characters
Keywords: Michoacán; civic pantheon; heroes; Morelos; Matamoros